BOLA PETIR SEBAGAI BENTUK PELEPASAN MUATAN LISTRIK: SUATU KAJIAN TEORITIKAL - Abduh, Syamsir (Jurnal Teknik Elektro, 2002)
In order to understand the atmospheric or lightning surges it would be important tounderstand the theory behind lightning.. This paper presents a review of literature of balllightning as a discharge phenomenon. It is assumed that ball lightning is produced andsustained by the electric fields associated with charges from a lightning strike dispersingalong preferred conducting paths in the earth. The theory gives an explanation of theformation, lifetime, energy sources and motion of a ball lightning.Keywords: ball lightning, lightning strike, discharge phenomenon